2014
DOI: 10.1007/s10886-014-0512-3
|View full text |Cite
|
Sign up to set email alerts
|

Plant Volatiles Influence the African Weaver Ant-Cashew Tree Mutualism

Abstract: Plant volatiles influence virtually all forms of ant-plant symbioses. However, little is known about their role in the mutualistic relationship between the African weaver ant and the cashew tree. In this study, we tested the hypothesis that cashew tree volatiles from plant parts most vulnerable to herbivory viz. inflorescence, leaves, and fruits, are attractive to weaver ants. Using behavioral assays, we show that these volatiles attract weaver ants but without significant difference in preference for any of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
0
4
0
3
Order By: Relevance
“…These results suggest that the presence of linalool, alloocimene, and neo-allo-ocimene, whether alone or in double or triple combinations, is positively associated with attractiveness to L. sativae. This possibility is supported by Egonyu et al (2013) and Wanjiku et al (2014), who also identi ed the compounds allo-ocimene and neo-allo-ocimene in cashew leaves, and showed, using behavioural bioassays, that as mixtures these compounds are attractive to the insect-pest Pseudotheraptus wayi (Heteroptera: Coreidae) and their natural enemy Oecophylla longinoda (Latreille) (Hymenoptera: Formicidae). In addition, olfactometry studies Guohui et al (2005) have found that the isolated linalool attracted adult females of L. sativae.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…These results suggest that the presence of linalool, alloocimene, and neo-allo-ocimene, whether alone or in double or triple combinations, is positively associated with attractiveness to L. sativae. This possibility is supported by Egonyu et al (2013) and Wanjiku et al (2014), who also identi ed the compounds allo-ocimene and neo-allo-ocimene in cashew leaves, and showed, using behavioural bioassays, that as mixtures these compounds are attractive to the insect-pest Pseudotheraptus wayi (Heteroptera: Coreidae) and their natural enemy Oecophylla longinoda (Latreille) (Hymenoptera: Formicidae). In addition, olfactometry studies Guohui et al (2005) have found that the isolated linalool attracted adult females of L. sativae.…”
Section: Discussionmentioning
confidence: 85%
“…Andrade et al 2016, Egonyu et al, 2013, Wanjiku et al 2014, and is present in considerable quantities in the genotypes of Citrus sp. less preferred by the psyllid Diaphorina citri, Kuwayama (Hemiptera: Psylidae)(Andrade et al 2016).…”
mentioning
confidence: 99%
“…Unfortunately, the ants fed with dsRNA SiOBPs, and Orco did not show any effects on the transcription and EAG levels at all. Feeding with dsRNA was reported to be a successful method for RNAi in some sap-sucking insects, such as the pea aphid ( A. pisum ) [ 21 , 22 ], white fly, ( Bemisia tabaci ) [ 23 ], and triatomine bug ( Rhodnius prolixus ) [ 24 ]. Even in S. invicta , the effect of the regulation of the pheromone-biosynthesis-activating neuropeptide (PBAN) on S. invicta survival has been investigated using RNAi.…”
Section: Discussionmentioning
confidence: 99%
“…Embora a produção e liberação de COVs sejam comuns no reino vegetal, os perfis quantitativos e qualitativos das misturas desses voláteis são distintos e dependem da espécie, cultivar e idade/estágio de desenvolvimento da planta (Niederbacher;Winkler;Schnitzler, 2015). Em cajueiro, embora alguns COVs tenham sido identificados (Egonyu et al, 2013;Wanjiku et al, 2014;Fancelli et al, 2018), estudos visando caracterizar esses compostos em diferentes genótipos ainda não foram realizados.…”
Section: Introductionunclassified